1987
DOI: 10.1111/j.1365-2621.1987.tb14095.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Serum Cholesterol Levels of Rats Fed Casein and Skim Milk Powdered Diets

Abstract: The temporal cholesterolemic patterns to skim milk powder (SMP) and reprocessed SMP (RSMP) diets were compared to diets containing casein or laboratory rat chow over a 24-day period. SMP was hypocholestetemic relative to casein in rats fed a 1% dietary cholesterol. Reprocessing of SMP resulted in an apparent loss of the relative hypocholesterolemic reponse of native SMP. Amino acid analysis of SMP and RSMP, showed only marginally lower lysine levels than casein; however, the IysineIarginine ratio was higher in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
(24 reference statements)
2
0
0
Order By: Relevance
“…Free lysine and peptide bound lysine residues are actively involved in the MR due to the presence of the lysine -amino group (34). Available lysine content of protein is decreased during the heating process in the presence of reducing sugar (35), and the extent of modification of protein lysine residues depends on MR conditions (36,37). The demonstration in the present study that loss of available lysine was greater for the Rib-casein, as compared to the Glc-casein GP, which in turn was greater than the Fru-casein GP, is additional evidence that casein glycation occurs differently depending on the sugar source.…”
Section: Ph and Color Changessupporting
confidence: 57%
“…Free lysine and peptide bound lysine residues are actively involved in the MR due to the presence of the lysine -amino group (34). Available lysine content of protein is decreased during the heating process in the presence of reducing sugar (35), and the extent of modification of protein lysine residues depends on MR conditions (36,37). The demonstration in the present study that loss of available lysine was greater for the Rib-casein, as compared to the Glc-casein GP, which in turn was greater than the Fru-casein GP, is additional evidence that casein glycation occurs differently depending on the sugar source.…”
Section: Ph and Color Changessupporting
confidence: 57%
“…The darker colour of the casein protein powder following thermal treatment suggests that a trace amount of lactose (a reducing sugar) was present, indicating the formation of non-enzymic Maillard browning reaction products (MRP). The loss of available lysine (Kanhai et al 1987) combined with the reduced protein digestibility associated with MRP (Lee et al 1977) are additional contributing factors to the reduced growth and nutrient malabsorption noted in this and other studies where animals were fed on HD proteins (Percival & Schneeman, 1979). Lee et al (1980) reported enhanced proteolytic activity and the production of only small amounts of macropeptides devoid of organic P in the intestinal contents of rats given a basal diet containing casein alone.…”
Section: Protein Digestibility and Yield Of Bioactive Peptidessupporting
confidence: 49%